Chamomile and Urtica dioica extracts improve immunological and histological alterations associated with polycystic ovarian syndrome in DHEA -induced mice - Maryam Shamsi; Ali Ganji; Ghasem Mosayebi; Ensieh Seif Amirhoseiny; Sepideh Shohani; Ali Ghazavi (BMC, 2023)
Abstract Background One of the novel mechanisms in the pathogenesis of Polycystic ovary syndrome (PCOS) is low-grade chronic inflammation. Chamomile (Matricaria recutita L.) and Nettle (Urtica dioica), with phytoestrogenic and antioxidant properties, are traditionally used to treat gynecological diseases. This study investigated the immune-modulating effects of these two plants. Methods Following the induction of PCOS by subcutaneous injection (SC) of Dehydroepiandrosterone (DHEA) in BALB / C mice. Mice were treated in five groups: Sham, PCOS, PCOS + Chamomile, PCOS + Nettle, and PCOS + Chamomile and Nettle for 21 days. Ovarian morphology, blood antioxidant capacity, the abundance of Treg cells, and expression of matrix metalloproteinase-9 (MMP-9), transforming growth factor-ß (TGF-ß), cyclooxygenase-2 genes (COX-2), and tumor necrosis factor-alpha (TNF-α) were measured. Results Folliculogenesis, Cystic follicles, and corpus luteum improved in the treatment groups (P < 0. 05). Treg cells in the DHEA group were significantly reduced compared to the Sham group (P < 0. 01). However, this decrease was not corrected in treatment groups (P > 0. 05). Total serum antioxidant capacity was significantly increased in the treatment group of Nettle and Chamomile + Nettle (P < 0. 05). The expression of MMP9 and TGFβ genes in the PCOS group was significantly higher than the Sham group (P < 0. 05), which the expression of MMP9 was corrected by treatment with Chamomile + Nettle extract (P < 0. 05). Conclusion Chamomile and Nettle extract may be an effective supplement in improving the histological and immunological changes of PCOS. However, more research is needed to confirm its effectiveness in humans.